Development of methyl isoxazoleazepines as inhibitors of BET. Issue 9 (1st May 2015) - Hewitt, Michael C.; Leblanc, Yves; Gehling, Victor S.; Vaswani, Rishi G.; Côté, Alexandre; Nasveschuk, Christopher G.; Taylor, Alexander M.; Harmange, Jean-Christophe; Audia, James E.; Pardo, Eneida; Cummings, Rich; Joshi, Shivangi; et al.
Graphical abstract